Analysis of Interest and Scientific Literacy Skills of Senior High School in Learning Physics - Dian Fadila; Suliyanah Suliyanah; Utama Alan Deta (Universitas Pendidikan Mandalika, 2020)
Scientific literacy is a person's ability to understand science, communicate science, and apply scientific knowledge to solve problems so that they have high attitudes and sensitivity to themselves and their environment in making decisions based on scientific considerations. This study aims to determine the understanding of high school students regarding scientific literacy and to determine the effect of high school students' interest in learning on science literacy learning outcomes. This study involved 201 high school students in Surabaya, Sidoarjo and Gresik. This study uses a mixed-method, namely, by using a quantitative approach and a qualitative approach. Quantitative analysis was perform using regression and correlation tests. The qualitative research obtains from questionnaires and interviews with students. The answers from students categorized into four levels, namely a score of 0 (did not answer the questions), score 1 (responded to questions but not quite right), score 2 (answered correctly) and score 3 (answered correctly) with exact categories). From the research results, it can conclude that students' understanding of scientific literacy is still low. The regression test where the significance value is 0.095> 0.05, which means that there is no influence of students' interest in learning on the results of students' scientific literacy skills, while the correlation test shows that the correlation between students' interests and the effects of scientific literacy skills (r) is 0.118. This indicates that there is a shallow relationship between students 'interest in learning and the consequences of high school students' scientific literacy skills. This research recommended that students can improve their understanding of scientific literacy by getting used to reading scientific literacy before learning begins so that students' interest in reading scientific phenomena increases.